2018
DOI: 10.1371/journal.pone.0198725
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the perspectives of users and beneficiaries of a community health worker mHealth tracking system for mothers and children in Rwanda

Abstract: IntroductionMobile Health (mHealth) programs have increasingly been used to tackle maternal and child health problems in low and middle income countries. However, few studies have evaluated how these programs have been perceived by intended users and beneficiaries. Therefore, we explored perceptions of healthcare officials and beneficiaries regarding RapidSMS Rwanda, an mHealth system used by Community Health Workers (CHWs) that was scaled up nationwide in 2013.MethodsWe conducted key informant interviews and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(81 citation statements)
references
References 14 publications
5
74
0
2
Order By: Relevance
“…namely mHealth programme, training and support of HCPs, a communication platform, data management platform, decision support and guideline (for HCPs) and mHealth message send to HCPs, reminder messages system, a communication platform, consultation platform (for pregnant women and mothers). Our ndings are supported by many other studies [45,48,55,64].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…namely mHealth programme, training and support of HCPs, a communication platform, data management platform, decision support and guideline (for HCPs) and mHealth message send to HCPs, reminder messages system, a communication platform, consultation platform (for pregnant women and mothers). Our ndings are supported by many other studies [45,48,55,64].…”
Section: Discussionsupporting
confidence: 91%
“…Health system organisation § HCPs training, supervision, resource availability, support and mobilisation [4,15,60,39,42,43,[46][47][48][49][50] § Mobile phone availability and distribution to HCPs [36] § Availability of HCPs [38,59] § HCPs and CHWs collaboration [38] Socio-demographic characteristic § Individual, pre-existing HCPs level of education, [37,40] § The language spoken by HCPs [44,50] Experience with technology § Technology adoption [40,43] Network infrastructure and connectivity § Availability of network and connectivity [44,64]…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…The lack of impact of RapidSMS on ANC services uptake was attributed to the infidelity in the implementation of the program. The study conducted in Rwanda by Musabyimana et al [47] on implementers' and community health workers' experiences of the RapidSMS program also identified challenges to the successful implementation of the program, which included lack of motivation and incentives, high turnover rates of CHWs, and lack of Our initial program theory is consistent with some existing models such as the Elaboration likelihood model (ELM) and the extensive Elaboration likelihood model (eELM) [48], and the Theoretical Domains Framework (TDF) [49] in behavior change. ELM and eELM by Adam et al [48] focused on Mobile Video intervention, which stipulates that the changes in attitude that predict a desired behavioral outcome such as exclusive breastfeeding can be explained in two pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although further research would be required to understand why RapidSMS had no impact on these indicators where there was enough room for improvement, we believe that the lack of impact could be explained, on the one hand, by the fact that the RapidSMS program was not implemented with perfect fidelity. For example, Musabyimana et al (2018) qualitative study undertaken in Rwanda to gather the experiences of the RapidSMS program implementers as well as community health workers with implementing RapidSMS identified challenges to successful implementation of RapidSMS including lack of motivation and high turn-over of CHWs, lack of regular CHW training and incentives [ 24 ]. Similarly, Condo et al (2014) identified several other factors (e.g., overwhelming workload and lack of supervision) that could hamper the effectiveness of the Rwandan community health program [ 25 ].…”
Section: Discussionmentioning
confidence: 99%